Health, illness and healthcare-seeking behaviour of the street dwellers of Dhaka City, Bangladesh: Qualitative exploratory study - Bente Kamal Tune, Samiun Nazrin; Hoque, Roksana; Naher, Nahitun; Islam, Nazia; Islam, Md. Mazedul; Ahmed, Syed Masud (BMJ Journals, 2022)
This article was published in BMJ Open by BMJ Journals [© Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2019-035663 The Journal's website is at: https://bmjopen.bmj.com/content/10/10/e035663